Pengaruh Kepemimpinan Transformasional dan Motivasi Kerja terhadap Kinerja Guru di Madrasah Aliyah Negeri 1 Batang Hari - Alifa Audy Angelya; Sukatin Sukatin; Zilawati Zilawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Teacher performance is the ability of a teacher to carry out his duties in an educational institution. Transformational leadership is leadership that includes organizational change efforts. Work motivation is a driving force that creates enthusiasm for someone to want to work together to achieve goals. This research is quantitative research, with a survey approach. The population in this study was all 28 teachers at Madrasah Aliyah Negeri 1 Batang Hari. The research sample where all members of the population were sampled was 28 people. For instrument testing, 20 people were carried out at different Madrasah Aliyah. The results of this research show that, partially, transformational leadership has a significant effect on teacher performance by 46.7%. This shows that the better the transformational leadership, the higher the teacher's performance. Work motivation has a significant effect on teacher performance by 52.2%. This shows that the better the work motivation, the higher the teacher's performance. Simultaneously there is a significant influence between transformational leadership and work motivation on teacher performance of 87%, with the obtained value of fcount ˃ ftable (83.392 ˃ 3.34). This shows reject H0 and accept Ha. This means that there is a significant influence between transformational leadership and work motivation simultaneously (simultaneously) on teacher performance at Madrasah Aliyah Negeri 1 Batang Hari.